The Ethical Aspects of Psychotherapeutic Assistance of Senior Adolescents with Different Conceptions About Welfare Relations with Parents - Pavliuk, Tetiana (Psychological Prospects Journal, 2018)
The article is devoted to the consideration of ethical aspects of psychotherapeutic assistanceof senior adolescents with different ideas about successful relations with parents. The methods of empirical study of the characterological specificity of senior adolescent’sconceptions about welfare relations with parents havebeengrounded. The results of empirical research have been presented, which allowed to establish the groups of adolescents by the character accentuations types. It has been revealed, that each of these groups has its own peculiarities of representations about welfare relationships with parents. It hasbeengrounded, that the same manifestations of parental attitude in mother’sandfather’s behaviour are differently perceived by adolescents of different types of character accentuations. The necessityof considerationof the specificity of the representations of senior adolescents with different types of character accentuations about the successful relations with parents in the formation of children-parents relationships has been emphasized. It hasbeen noted, that discrepancy of parents’ real attitude towardsa child and its manifestations in their behaviour andtowards adolescents expectations, leads to the destruction of children-parents relationships, that, in case of their aggravation, leads to the appearance of a complex of personality problems and, as a consequence, to mental health disturbance of children as well as parents. The attention is focused on the necessity of solving this problem by professional psychotherapeutic means. The main ethical principles and rules of psychotherapeutic assistance in solving the problem of coordination and harmonization of relations between senior adolescents and parents have been highlighted, including the principles of informed consent, confidentiality, client’s non-impairment, client’s welfare, competence and responsibility of a psychotherapeutist. The main controversial issues in compliance with the ethical principles and rules in psychotherapist’s work with senior adolescence age children have been formulated.